Social scholarship: Reconsidering scholarly practices in the age of social media. (19th March 2014) - Greenhow, Christine; Gleason, Benjamin
Abstract This conceptual exploration inquires, what is scholarship reconsidered in the age of social media? How ought we to conceptualize social scholarship—a new set of practices being discussed in various disciplines? The paper offers a critical examination of the practical and policy implications of reconsidering scholarship in light of social media's affordances toward a conceptualization of social scholarship. For each dimension of Boyer's original framework, we explain its epistemologies and practices. Next, we take a critical approach to inquiring how each dimension, reconsidered through the lens of social scholarship values and social media affordances, might be envisioned today. This exploration provides concrete examples of how scholars might enact social scholarship with what benefits and challenges.